The transition from intra to extra-uterine life in late preterm infant: a single-center study. Issue 1 (December 2016) - De Carolis, M.; Pinna, G.; Cocca, C.; Rubortone, S.; Romagnoli, C.; Bersani, I.; Salvi, S.; Lanzone, A.; De Carolis, S.
Abstract Background Infants born at 34 to 36 weeks of gestation (late preterm) are at greater risk for adverse outcomes than those born at 37 weeks of gestation or later. Aim of this paper is to examine risk factors for late preterm births and to investigate the complications of the transition period in late preterm infants (LPIs). Methods All consecutive late preterm deliveries, excluded stillbirths, were included. Maternal and neonatal data, need for delivery room resuscitative procedures, temperature at birth (T1) and two hours after the admission (T2) were analyzed in all LPIs stratified by Gestational Age (GA) and divided into three groups (34, 35 and 36 weeks). Results Two hundred seventy-six LPIs were analyzed. Pregnancy complications were present in 72 mothers (26.1 %), more frequently at 34 weeks of gestation respect to 35 and 36 weeks (p = 0.008, p = 0.006 respectively). Forty seven LPIs (17.1 %) needed for any resuscitation and 37 (13.4 %) were ventilated at birth. LPIs at 34 weeks were significantly more likely to receive ventilation respect to those at 35 and 36. At T1 the mean temperature resulted lower at 34 weeks respect to 36 weeks (p = 0.03). At T2 respect to T1, the rate of normothermic neonates increased at 35 and 36 weeks (p = 0.003, p = 0.005, respectively). Hypoglicemia rate was similar among the groups; 66.7 % of hypoglicemic neonates were hypothermic at T1. The rate of respiratory diseases and NICU admission decreased with increasing GA. Higher number of neonates ventilated at birth developed respiratory disorders respect to those unventilated (40.5 % vs 8.4 %;p < 0.001). Conclusions Transition period in LPIs may become critical, as resuscitation strategies can be required and heat loss can occur. LPIs, especially at 34 gestational weeks, are higher-risk group needing adequate and targeted management at birth.